The clinical legal medicine: a need for quality of care and patient’s safety. A single center five-year experience - Bolcato, Matteo; Russo, Marianna; Sanavio, Matteo; Rodriguez, Daniele; Aprile, Anna (Acta Biomedica Atenei Parmensis, 2020)
Introduction. Clinical legal medicine is a branch of legal medicine that takes place in a clinical setting approaching the patient’s bedside and using a particular attention not only for conceptual or normative references but also for every possible medical and social aspect. Material and methods. The requests of medico-legal opinions received by the Department of Legal Medicine of a large university hospital were retrospectively collected over a 5-years period. The analysis focused on the recurrence rate of the requests and the most common medico-legal issues to be solved in a clinical context, differentiating between adult and minor patients. Results. The collected medico-legal advices amounted to 448. The most clearly involved clinical area was Medicine (54%) followed by Gynecology and Obstetrics (15.6%), Pediatrics and Surgery (10.7%). The requests concerning patient’s self-determination in therapeutics choices, including refusal of proposed treatments, covered almost one-half of total casuistry. The designation of support administrator represented also a relevant issue (20.5%). In case of minors, the queries related to reporting crimes were three times higher than in adults, while the appointment of a support administrator was never requested. Conclusion. Clinical legal medicine, through medico-legal advices, plays a primary role in contributing to the safeguarding of health and to the decision-making process of clinicians.